Մեծ եղեռնի ընթացքում արեւմտահայութեան կրած մարդկային եւ նիւթական կորուստները վիճակագրելու Կ. Պոլսի Հայոց Պատրիարքարանի փորձերը 1919–1920 թուականներին (ըստ Երուսաղէմի Հայոց Պատրիարքարանի արխիւի նիւթերի) - Ռոբերտ Թաթոյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Одним из основных направлений деятельности Константинопольского Армянского патриархата в 1919-1920 годах стал сбор данных о численности армянского населения в предверии геноцид а, а также людских и материальных потерях, понесенных армянами вовремя депортации и резни. Collection of data on the number of the Armenian population prior to the genocide, as, well ason human and material losses suffered by the Armenians during deportations and massacres, was one of the main course of actions of the Armenian Patriarchate of Constantinopole in 1919-1920.
Keywords: History; Armenian Genocide (1915)